Utilization Of Chitosan As A Natural Preservative Against Catfish - Nurhayati, Nurhayati; Ridwanto, Ridwanto; Sartika Daulay, Anny; Andi Syahputra, Ricky; Rani, Zulmai (Publisher Cv. Inara, 2022)
Shrimp in Indonesia are generally exported abroad after removing the head, tail, and skin. One alternative to the use of shrimp shell waste that has high economic value is processing shrimp shells into chitosan. The purpose of this study was to determine the shelf life of catfish using chitosan and to determine the optimal concentration of chitosan in catfish preservation. Chitosan applied to catfish showed that in the addition of a 0% chitosan solution, it had a shelf life of up to day 2 for 48 hours for a 0.5 solution; 1; 1.5 and 2% shelf life up to day 5 or for 120 hours. The most optimal concentration of chitosan for use in catfish is a 2% chitosan solution, and the total plate number (ALT) test meets the requirements of the SNI standard so that it can still be consumed.